2022
DOI: 10.3390/nu14193966
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Prevents Chondrocyte Matrix Degradation in Rats with Experimentally Induced Osteoarthritis by Inhibiting Nuclear Factor-κB via SIRT1

Abstract: Osteoarthritis (OA) is a common degenerative joint disease characterized by an imbalance of cartilage extracellular matrix (ECM) breakdown and anabolism. Melatonin (MT) is one of the hormones secreted by the pineal gland of the brain and has anti-inflammatory, antioxidant, and anti-aging functions. To explore the role of MT in rats, we established an OA model in rats by anterior cruciate ligament transection (ACLT). Safranin O-fast green staining showed that intraperitoneal injection of MT (30 mg/kg) could all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…The treatment with IL-1β induced upregulation of MMP-3, MMP-9, MMP-13, ADAMTS-4, COX-2 and iNOS levels, while downregulation of chondrogenic marker COL2A1 in human mesenchymal stem cells (hMSCs) and chondrocytes. However, melatonin significantly mitigated the detrimental effects caused by IL-1β ( 154 , 155 , 158 ). By inhibiting the JAK2/STAT3 signaling pathway, melatonin effectively reduced the levels of MMP-3, MMP-9, and MMP-13, thereby attenuating cartilage degradation ( 138 ) ( Figure 3 ).…”
Section: Melatonin Targeting Oxidative Stress Inflammation and Chondr...mentioning
confidence: 96%
See 2 more Smart Citations
“…The treatment with IL-1β induced upregulation of MMP-3, MMP-9, MMP-13, ADAMTS-4, COX-2 and iNOS levels, while downregulation of chondrogenic marker COL2A1 in human mesenchymal stem cells (hMSCs) and chondrocytes. However, melatonin significantly mitigated the detrimental effects caused by IL-1β ( 154 , 155 , 158 ). By inhibiting the JAK2/STAT3 signaling pathway, melatonin effectively reduced the levels of MMP-3, MMP-9, and MMP-13, thereby attenuating cartilage degradation ( 138 ) ( Figure 3 ).…”
Section: Melatonin Targeting Oxidative Stress Inflammation and Chondr...mentioning
confidence: 96%
“…Zhao et al. likewise testified that melatonin downregulates IL-1β-induced phosphorylation levels of P65 and IκBα in chondrocytes via SIRT1 pathways, thus abolishing NF-κB activation to function in cytoprotective and anti-inflammatory effects ( 155 ). It has been demonstrated that the toll-like receptor (TLR) mediates inflammatory responses triggered by chemical and physical stressors, such as cytokines and mechanical damage, ultimately leading to the development of OA ( 163 ).…”
Section: Melatonin Targeting Oxidative Stress Inflammation and Chondr...mentioning
confidence: 99%
See 1 more Smart Citation
“…SIRT1, a nicotinamide adenine dinucleotide (NAD)-dependent nuclear histone deacetylase, has been reported to downregulate the activity of NF-κB in rat chondrocytes ( 54 ). SIRT1 promotes the deacetylation of p65 and suppresses the nuclear translocation of NF-κB, protecting against the inflammatory responses in articular chondrocytes and the development of OA ( 55 ).…”
Section: Nf-κb Signaling In the Physiology And Pathogenesis Of Chondr...mentioning
confidence: 99%
“…Moreover, dysfunction of mitochondria has also been reported in the occurrence of OA diseases 7,15 . Some small molecules such as Urolithin A and melatonin have been shown to reduce cartilage damage and restore cartilage function in the progress of OA by improving mitochondrial function in chondrocytes 16,17 . Therefore, exploring the influence mechanisms of mitochondrial morphology and function changes in chondrocytes is conducive to the studies of new treatments for OA.…”
Section: Introductionmentioning
confidence: 99%